THE RELATIONSHIP BETWEEN HELICOBACTER PYLORI AND ARTERIAL HYPERTENSION WAS ANALYZED - Boboyorova D. N. (Journals Park Publishing, 2023)
The literature review analyzes studies on the role of Helicobacter pylori in the development of hypertension in recent years, using data from the scientific literature, important data aimed at solving the mutual pathogenetic relationship between the two problems. The result of several tests is H. pylori: people with pylori have a higher risk of developing hypertension than people who are not infected. H. pylori has been shown to be the pathological mechanisms of pylori's effect on the body. H. pylori The mutual pathogenetic dependence in the development of pylori and hypertension is based on data on the occurrence of endothelial dysfunction, which is accompanied by an increase in the number of inflammatory cytokines, homocysteinemia, and a decrease in vitamin D.
Keywords: arterial hypertension, Helicobacter pylori, risk factor, endothelial dysfunction, pathogenetic dependence, homocysteinemia.